Ojibwe Perspectives Toward Proper Wolf Stewardship and Wisconsin’s February 2021 Wolf Hunting Season - Gilbert, Jonathan H.; David, Peter; Price, Michael W.; Oren, Jenny (Frontiers in Ecology and Evolution, 2022)
In February 2021, the Wisconsin DNR implemented a wolf season in which >20% of the population was killed in 63 hours. Wisconsin’s Ojibwe tribes had a visceral reaction to this killing. This paper provides a perspective for this reaction by reviewing the Ojibwe relationship with Ma’iingan. This relationship maintains that ma’iingan and Ojibwe are to be considered relatives whose fates are intertwined. Ma’iingan and Ojbwe have lived parallel histories, suffering from the effects of colonization, the decimation of wolf populations and decline of tribal culture. The Ojibwe tribes ceded vast territories in treaties with the US while retaining common use rights, including the right to hunt and fish. These rights were reaffirmed just as wolves were reestablishing themselves in Wisconsin. The tribes continue to strengthen their culture, while wolf populations continue to recover. By examining these comparative histories, it becomes apparent that “whatever happens to one happens to the other”. Unfortunately, Ma’iingan were not adjudicated during the Wisconsin treaty case, creating uncertainty over how the relationship between the Ojibwe and Ma’iingan is to be respected by the state. The tribes believe their treaty right includes protection for wolves, so that wolves can fulfill their cultural and ecological purposes. It is unclear if state and tribal wolf objectives can be meshed. Tribes maintain that Ma’iingan should determine their own population levels, in order to provide ecological and cultural benefits. A respectful and appreciative relationship should be maintained so that the future well-being of both Ma’iingan and the Ojibwe will be assured.